Transformation of Islamic Religious Education in the Era of the Industrial Revolution 4.0 and Society 5.0 - Muhammad Azhari; Hidayat Ma’ruf; Husnul Yaqin; Hamdan Hamdan (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
Educational transformation has become inevitable amid the development of digital technology in the era of the Fourth Industrial Revolution and the concept of Society 5.0. Islamic Religious Education (IRE) is required not only to focus on the transfer of religious knowledge but also to adapt to technological and informational advancements, as well as the needs of modern society. This study aims to analyze the forms of transformation in Islamic Religious Education in addressing the challenges of the Fourth Industrial Revolution and Society 5.0, as well as their implications for the learning process. This study employs a qualitative method using a literature review approach (library research) through the analysis of various relevant literature, scientific journals, books, and documents related to the research topic. Data analysis techniques involve data reduction, data presentation, and the systematic drawing of conclusions. Research findings indicate that the transformation of Islamic Religious Education in this era encompasses the use of digital technology in learning, the strengthening of digital literacy and religious character, and the development of innovative, student-centered learning models. Furthermore, integrating Islamic values with 21st-century skills is a crucial step in preparing a generation that is religious, critical, creative, and adaptable to the changing times. Thus, the transformation of Islamic Religious Education in the era of the Fourth Industrial Revolution and Society 5.0 emphasizes not only technological proficiency but also the reinforcement of spiritual, moral, and social values in modern society.